Strategi Komunikasi Islam Berbasis Tabayyun dalam Menghadapi Penyebaran Hoaks di Media Sosial - Sulaiman Sulaiman; Arum RosaAsmarani; Muhamat Aldi; Meli Juniarti; Wan DevinaHaye (Khulasah : Islamic Studies Journal, 2026)
This study aims to formulate an Islamic communication strategy based on tabayyun for responding to the spread of hoaxes on social media. The research uses a qualitative library research design by synthesizing recent journal articles, official reports, and digital literacy documents published between 2021 and 2026. The analysis focuses on the relationship between the Islamic principle of verification, the dynamics of misinformation, and practical communication steps for Muslim social media users, educators, preachers, and community institutions. The findings show that tabayyun can be developed into a preventive, corrective, and educational strategy through five stages: receiving information carefully, checking source credibility, comparing evidence, considering social harm, and communicating corrections ethically. The study concludes that tabayyun is not only a moral teaching but also a communication framework that integrates digital literacy, fact-checking, ethical responsibility, and communal care.